The Computer in Art. - Reichardt, Jasia (London : Studio Vista Limited, 1971)
Alsleben, Kurd ; Computer Technique Group ; Csuri, Charles ; Hammersley, Frederick ; Harmon, Leon D. ; Hertlein, Grace ; Julesz, Bela ; Knowlton, Kenneth C. ; Mallary, Robert ; Metzger, Gustav ; Mezei, Leslie ; Mondriaan, Piet ; Nake, Frieder ; Nash, Katherine ; Nees, Georg ; Noll, A. Michael ; Passow, Cord ; Robbins, Donald K. ; Schroeder, M.R. ; Schwartz, Lillian ; Siden, F.W. ; Struycken, Peter ; Sumner, Lloyd ; Tsai, Wen Ying ; VanDerBeek, Stan ; williams, Richard
Engels
boek